Adherence to Hepatitis C Therapy in a Shelter-Based Education and Treatment Model Among Persons Experiencing Homelessness. (25th September 2021) - Powell, Jesse; Ricco, Margaret; Naugle, Jessica; Magee, Catherine; Hassan, Hayat; Masson, Carmen; Braimoh, Grace; Zevin, Barry; Khalili, Mandana
Abstract: Background: Medication adherence is a common reason for treatment deferment in persons experiencing homelessness. We evaluated adherence to hepatitis C virus (HCV) therapy following HCV education in a shelter-based care model. Methods: Prospective study conducted at 4 homeless shelters in Minneapolis, Minnesota and San Francisco, California from November 2018 to January 2021. Sixty-three patients underwent HCV education and treatment. Multivariable modeling evaluated factors associated with (1) medication and (2) overall (composite score of medication, laboratory, and clinic visit) adherence. Results: Median age was 56 years; 73% of participants were male, 43% were Black, 52% had psychiatric illness, and 81% used illicit drugs and 60% used alcohol in the past year. Following education, 52% were extremely confident in their ability to be adherent to HCV therapy. Medication adherence by patient and provider report was 88% and 48%, respectively, and 81% achieved HCV cure. Active alcohol use was associated with less confidence in medication adherence (43% vs 78%, P = .04). Older age was positively (coefficient = 0.3) associated with overall adherence to HCV treatment whereas prior therapy was associated with both medication (odds ratio, 0.08) and overall treatment (coefficient = –0.87) nonadherence. Conclusions: Despite imperfect adherence, sustained virologic response rates were still high. Expanding opportunities to treat persons experiencing homelessness in a structured and supportive setting is critical to HCV elimination efforts.